The Effect of Innovative Teaching Methods on Elementary School Students’ Academic Achievement in Indonesia: A Meta-Analysis - Ardiansyah, Ardiansyah; Widati, Juriah; Putri, Dinda Meilani; Kelen, Redemptus Pulo; Perwitasari, Ningrum (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2026)
Innovative learning models such as Project-Based Learning, Problem-Based Learning, and Discovery Learning have been widely promoted in Indonesian elementary schools to improve student engagement, yet their overall effect on academic achievement remains scattered across individual, small-scale studies. This study aims to examine the effect of innovative learning on student academic achievement in Indonesia using a meta-analysis approach. Research data were obtained from 20 articles that met the inclusion criteria, namely, quantitative studies with complete data including sample size, mean scores, and standard deviations, published between 2012 and 2021. Data analysis was conducted using a random-effects model with the assistance of JASP software to calculate effect sizes, heterogeneity, and publication bias. The results indicate a high level of heterogeneity (I² = 90.5%), suggesting variations across studies, such as differences in the innovative learning models used (e.g., PjBL, PBL, and others), sample characteristics, grade levels, and learning contexts. The Forest Plot analysis results showed a summary effect size of 0.68 with a 95% confidence interval of 0.55 to 0.81, indicating that innovative learning has a positive effect on student academic achievement. Additionally, the Funnel Plot results using the Trim and Fill method showed no publication bias, so the findings of this study can be considered valid and reliable. Thus, innovative learning has been proven effective in improving student academic achievement in Indonesia.